THE BANK'S ADAPTATION TO THE MODERN TECHNOLOGY IN A COMPETITIVE ENVIRONMENT - Останкова, Лариса; Шевченко, Наталья; Здерева, Екатерина (International Journal of Economic Practice and Policy, 2016)
Actual problems of formation of long-term development directions of the bank and the possibility of adjusting objectives on the basis of monitoring and forecasting economic indicators are considered.
Keywords: BANK; banking competition; business process; economic indicators; forecasting; risk; optimization